Risk Management Analysis of Future Package Financing (PMD) with a Murabaha Contract at PT. Bank BTPN Syariah Rantau Prapat Branch Office - Elsa Hafe Eza Lubis; Maryam Batubara; Muhammad Arif (Quantitative Economics and Management Studies, 2023)
This study aims to analyze the risk management of the Future Package (PMD) financing with a Murabaha contract at PT. Bank BTPN Syariah Rantau Prapat Branch Office. PMD is one of the financing products offered by Islamic banks, and a Murabahah contract is one of the financing mechanisms in the Islamic banking system. The research method used is a case study with a qualitative approach. Data was collected through interviews with related parties at PT. Bank BTPN Syariah Rantau Prapat Branch Office and analysis of documents related to risk management. The results of the research show that PT. Bank BTPN Syariah Rantau Prapat Branch Office has implemented good risk management in PMD financing with a Murabahah contract. The identified risks, such as credit risk, liquidity risk, operational risk and market risk, have been properly managed through various policies and procedures that have been established. However, there are several challenges faced by banks in managing PMD financing risks with Murabaha contracts, such as market fluctuations and regulatory changes that affect the Islamic banking business. This research is expected to contribute to the development of PMD financing risk management with a Murabaha contract at PT. Bank BTPN Syariah and provide insights for other Islamic financial institutions in managing risk more effectively and efficiently.